UZBEKISTAN IN THE REPUBLIC ADULTS BETWEEN METABOLIC DISORDERS WITH RELATED EXCESS WEIGHT OF THE CIRCUMSTANCES SPREAD - E. Y. Sultanov; Rakhimov Bakhodir Bakhtiyorovich; Saidkarimova Nozimahon; Yahyoyeva Diloram (Bright Mind Publishing, 2025)
Last in years world on a scale food factors chronic uninfected diseases in development place much deep is being studied. Research this shows that excessive weight and obesity, atherosclerosis, hypertension, carbohydrate exchange disorder, metabolic syndrome, immune shortage cases such as of diseases increase one row "external" with " factors " related. Their the most important: nutrition of the composition fast change (nutrients ratio violation), physical activity reduction of stress increase.
Keywords: Excess weight, metabolic disorders, epidemiology, population health, regional differences.